Control of yeast alpha-specific genes: evidence for two blocks to expression in MATa/MAT alpha diploids. - Ammerer, G (1985)
In yeast alpha cells, the product encoded by the MAT alpha 1 gene of the mating-type locus is required for transcription of at least two genes, STE3 and MF alpha 1. To learn whether the lack of the MAT alpha 1 product in a and a/alpha cells is sufficient to explain the failure to express STE3 and MF alpha 1 in these cells, we have provided MAT alpha 1 product via a hybrid gene that circumvents the normal regulation of the MAT alpha 1 gene. We find by RNA blot analysis that provision of MAT alpha 1 protein permits production of STE3 and MF alpha 1 mRNA in a cells but not in a/alpha cells. These data suggest the existence of an additional regulatory mechanism that prevents expression of alpha-specific genes in a/alpha cells, even when MAT alpha 1 product is present. This regulatory mechanism appears to control expression of STE3 and MF alpha 1 at the transcriptional level rather than at the posttranscriptional level, because we show that MF alpha 1 mRNA supplied from a constitutive promoter is translated and processed in a/alpha cells to yield functional alpha-factor pheromone. This result shows further that a/alpha cells possess all the machinery necessary for pheromone maturation, even though these cells do not normally carry out these reactions.